1974
DOI: 10.1021/jm00256a003
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic analgesics. Synthesis and pharmacology of the diastereoisomers of N-[3-methyl-1-(2-phenylethyl)-4-piperidyl]-N-phenylpropanamide and N-[3-methyl-1-(1-methyl-2-phenylethyl)-4-piperidyl]-N-phenylpropanamide

Abstract: The antagonistic property of ethyl p-(4-ethoxycarbonyl-4-phenyl-l-piperidinoethyl)fumaranilate ( 5) was investigated. Compound 5 was found to antagonize morphine analgesia in a complex manner which could not be described as a simple competitive or noncompetitive type. The antagonism, however, lasted for over 6 hr suggesting that 5 has a high affinity for the analgesic receptors. Compound 5 appeared to possess dependence liability in the single-dose suppression test. In the electrically stimulated isolated guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 5 publications
0
66
0
1
Order By: Relevance
“…Second, chimeras /␦1 and ␦/3 may assume favorable conformations for SUPERFIT to form a covalent bond with the receptor, whereas chimeras ␦/1, /␦3, and /␦4 do not. When [ Although SUPERFIT is a ␦ selective irreversible ligand, its parent compound, cis-(ϩ)-3-methylfentanyl is a selective agonist (27). Similarly, fentanyl is a selective agonist for the receptor (28), yet its isothiocyanate derivative, FIT, is a selective irreversible ligand for the ␦ receptor (29).…”
Section: Resultsmentioning
confidence: 99%
“…Second, chimeras /␦1 and ␦/3 may assume favorable conformations for SUPERFIT to form a covalent bond with the receptor, whereas chimeras ␦/1, /␦3, and /␦4 do not. When [ Although SUPERFIT is a ␦ selective irreversible ligand, its parent compound, cis-(ϩ)-3-methylfentanyl is a selective agonist (27). Similarly, fentanyl is a selective agonist for the receptor (28), yet its isothiocyanate derivative, FIT, is a selective irreversible ligand for the ␦ receptor (29).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds had high potential for abuse, because of their ease of synthesis and high analgesic activity. The structures of fentanyl (1) and 11 synthesized analogues (2-12) examined in this study are shown in Tables 1-4. Although there are a number of reports regarding the analgesic activities of some of these analogues [8][9][10][11][12][13][14][15], there have been only a few reports on the actually abused analogues [8]; there have been no reports on α-methylfentanyl (2), the most widely abused analogue. Furthermore, comparison of their analgesic activities with those of morphine and fentanyl was not described.…”
Section: Introductionmentioning
confidence: 99%
“…TMF has so far been involved only in relatively short-lived epidemics [3,4]. This is obviously due to the high potency of this opioid drug and the associated dosing problems: the cis-(+)-isomer of TMF is approximately 7,000 times as potent as morphine while the trans-(±)-isomer is approximately 1,000 times as potent [5]. Figure 1 shows the chemical structures of fentanyl, alpha-methylfentanyl, and cis-and trans-TMF.…”
Section: Introductionmentioning
confidence: 99%